Synergy of Faith and Knowledge: Financial Management and Sexual Reproductive Health Education for Pre-Marital Youth in the Java Christian Church, Jatiluhur, Bekasi - Yusuf Rombe M. Allo; Melinda Malau; Louisa A. Langi; Claudia Valoryn Rombe; Delvia Sari Lim (IKRA-ITH ABDIMAS, 2026)
This community service initiative was designed to enhance comprehension amongpremarital adolescents and adult couples at the Javanese Christian Church (GKJ) JatiluhurCongregation in Jakasampurna, Bekasi, West Java, concerning the crucial significance offinancial management and sexual reproductive education. The program concentrated ondisseminating precise and thorough information about reproductive health, encompassingbiological and psychological changes, the prevention of sexually transmitted infections,and the principles of sustaining healthy and responsible sexual conduct. Simultaneously, itemphasized that robust family financial management, which includes budgeting, debtmanagement, establishing shared financial objectives, and preparing emergency funds,constitutes a crucial foundation for couples planning to get married. Employingmethodologies such as interactive counseling, discussions, and question-and-answersessions, the activity ensured participants acquired practical and applicable insights. Theprogram effectively elevated participants' understanding of sexual reproductive health andempowered them to make well-informed decisions regarding both their reproductive healthand sustainable financial management. It is recommended that comparable programs beextended to other religious congregations to bolster marital success holistically.Keywords: financial management, pre-marital, health, reproduction.